Rearrangements in the retino-geniculate projections of rats following ablation of the superior colliculus in infancy. - Reese, B; Cowey, A (1985)
The superior colliculus was bilaterally or unilaterally ablated at different early postnatal ages in rats. When adult, each rat received a unilateral eye injection of Horseradish peroxidase to reveal the crossed and uncrossed retinal terminal fields within the dorsal lateral geniculate nucleus. Collicular ablation in the first seven days after birth, but not thereafter, produced a small hole or vacancy within the contralateral retinal terminal field which was occupied by an aberrant ipsilateral retinal terminal field. These rearrangements in the retino-geniculate projections occurred in the caudal quarter of the nucleus dorso-laterally just beneath the optic tract, solely ipsilateral to the ablated colliculus. Possible causes of the formation of these rearrangements are discussed, and similarities with other aberrant retinal projections following early damage to the visual system are considered.